Crosstalk Between Oxidative Stress and Endoplasmic Reticulum (ER) Stress in Endothelial Dysfunction and Aberrant Angiogenesis Associated With Diabetes: A Focus on the Protective Roles of Heme Oxygenase (HO)-1 - Maamoun, Hatem; Benameur, Tarek; Pintus, Gianfranco; Munusamy, Shankar; Agouni, Abdelali (Frontiers in Physiology, 2019)
Type-2 diabetes prevalence is continuing to rise worldwide due to physical inactivity and obesity epidemic. Diabetes and fluctuations of blood sugar are related to multiple micro- and macrovascular complications, that are attributed to oxidative stress, endoplasmic reticulum (ER) activation and inflammatory processes, which lead to endothelial dysfunction characterized, among other features, by reduced availability of nitric oxide (NO) and aberrant angiogenic capacity. Several enzymatic anti-oxidant and anti-inflammatory agents have been found to play protective roles against oxidative stress and its downstream signaling pathways. Of particular interest, heme oxygenase (HO) isoforms, specifically HO-1, have attracted much attention as major cytoprotective players in conditions associated with inflammation and oxidative stress. HO operates as a key rate-limiting enzyme in the process of degradation of the iron-containing molecule, heme, yielding the following byproducts: carbon monoxide (CO), iron, and biliverdin. Because HO-1 induction was linked to pro-oxidant states, it has been regarded as a marker of oxidative stress; however, accumulating evidence has established multiple cytoprotective roles of the enzyme in metabolic and cardiovascular disorders. The cytoprotective effects of HO-1 depend on several cellular mechanisms including the generation of bilirubin, an anti-oxidant molecule, from the degradation of heme; the induction of ferritin, a strong chelator of free iron; and the release of CO, that displays multiple anti-inflammatory and anti-apoptotic actions. The current review article describes the major molecular mechanisms contributing to endothelial dysfunction and altered angiogenesis in diabetes with a special focus on the interplay between oxidative stress and ER stress response. The review summarizes the key cytoprotective roles of HO-1 against hyperglycemia-induced endothelial dysfunction and aberrant angiogenesis and discusses the major underlying cellular mechanisms associated with its protective effects.